Analysis of Consumer Behavior Towards Product Groups at Indomaret Sudiang Raya - Paulus Djohan Lolo; Nurdiansyah Nurdiansyah (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
Effective marketing necessitates a profound understanding of consumer behavior, and the SOR Model (stimuli-organisms-response) stands out as a crucial theory in this domain. This model identifies three stages in the purchasing process: stimuli, organism (consumer's mind), and response. In this study, we explore consumer responses within various product categories, seeking to unveil patterns in decision-making processes. The experiment at Indomaret Sudiang Raya involved observing 146 randomly selected individuals, ensuring gender balance among respondents. The research encompassed three key sections: initial purchase goals and desires, observations of consumer behavior, and a survey on reasons for purchasing products. Our findings shed light on diverse consumer behaviors, encompassing immediate purchases, indecisiveness, analytical reviews, and non-stop behavior across different product categories. Certain product groups were less frequently purchased, suggesting dynamic shifts in consumer preferences over time. We delved into the cognitive and personal responses of Indomaret shoppers, revealing distinct patterns such as experiential behavior (purchasing known products) and analytical behavior (meticulously analyzing options before purchasing). The study identified nuances across product categories, providing valuable insights into the intricate landscape of consumer decision-making processes.